D01 Updating of guidelines for the molecular genetic predictive test in Huntington's disease (1994). (16th November 2010) - MacLeod, R; Tibben, A; Frontali, M
Abstract : Background: Guidelines for the molecular genetic predictive testing in Huntington's disease (HD) were issued in 1994, soon after the discovery of the gene. Since then, the research on HD has made remarkable advancements and a considerable amount of experience was acquired by centres offering the presymptomatic and prenatal HD tests. After 16 years the EHDN WG on Genetic Testing and Counselling thought that some recommendations should be updated and some added, on the basis of scientific evidence and documents collected so far. Methods: WG participants, including members of the lay association, psychologists, neurologists, geneticists, genetic counsellors and ethicists from all over Europe were divided into subgroups, each devoted to a particular topic. Each subgroup had to collect the relevant scientific literature and documents, discuss the possible changes and propose an update. The updates proposed by each subgroup were discussed in plenary meetings. The proposed updates were posted on the EHDN website to be electronically discussed by EHDN members. A revised version will be submitted to IHA and WFNHDRG members for further discussion. The final approval is foreseen at the World Congress on Huntington's Disease in Melbourne, September 2011. Results: The following topics were selected for review: testing of minors (Rec 2.), lab standard of accuracy (Rec 2.8), limitation of the test information about age of onset and intermediate/low penetrance alleles (5.2.3, 5.2.4) and discrimination (4.2, 5.3) In addition, new guidelines were proposed, dealing with PGD and information about clinical trials. The proposed updates will be reported at the meeting in Prague as well as the evidence and documents on which they are based. Conclusions: The results indicate the need to fill the gap between the present guidelines and the state of the art in research and ethical elaboration. Comments, reactions and suggestions from the EHDN Congress participants are essential for the update validation.